Redefined prophecy as Deuteronomic alternative to divination in Deut 18:9-22 - Bosman, H L (Acta Theologica, 1996)
Anthropological research has shown that no rigid distinction can be maintained between prophets, priests, diviners and necromancers. All of them function as religious intermediaries and act as repositories and interpreters of religious tradition and as sources of divine knowledge. In Deut 18:9-22 the link between diviners, soothsayers, sorcerers, necromancers and prophets is sometimes interpreted as an indication of a lesser view of prophecy in pre-exilic Israel. This paper advocates a more appreciative perspective of divination that acknowledges its close link with prophecy and accepts a much closer similarity between Canaanite and Israelite religion. The vehemence of the critique against divination presupposes the significant religious role played by diviners in Babilonian, Canaanite and Israelite society. This also caused a Deuteronomic redefinition of the office and function of the prophets as the most important remaining religious leaders in Babilonia and to enable the maintenance of power within the centralized religion of the post-exilic Jewish community in Palestine.